ANALISIS PERHITUNGAN, PENYETORAN DAN PELAPORAN PAJAK PERTAMBAHAN NILAI PADA PERUM BULOG KANTOR WILAYAH SUMATERA SELATAN DAN BANGKA BELITUNG - Masnoni, Masnoni (Institut Rahmaniyah Sekayu, 2023)
The purpose of this study is to find out how the calculation, deposit, and value added tax report at Perum BULOG South Sumatra and Bangka Belitung regional offices and their compliance with Law No. 42 of 2009 and generally applicable tax accounting principles. The writer used descriptive method. The research was conducted at Perum BULOG South Sumatra and Bangka Belitung regional offices as a taxable company. Data obtained were data of value added tax, output tax invoice, input tax invoice of 2021. The research result showed that Perum BULOG South Sumatra and Bangka Belitung regional offices had cconducted the calculation procedure, deposit, and value added tax report according to UU No. 42 of 2009. Nevertheless, there was a difference because of the rounding using government’s system. The recording was in accordance with generally accepted accounting requirements.